The evolution of the national licensing system of health care professionals: a qualitative descriptive case study in Lao People's Democratic Republic - Miwa Sonoda; Bounkong Syhavong; Chanphomma Vongsamphanh; Phisith Phoutsavath; Phengdy Inthapanith; Arie Rotem; Noriko Fujita (BMC, 2017)
Abstract Background The introduction of a systematic framework for the licensing of health care professions, which is a crucial step in ensuring the quality of human resources for health (HRH), is still evolving in Lao People's Democraic Republic. The aim of this study was to review and document the evolution of Lao HRH policies and the development of its national licensing system. Case presentation A qualitative descriptive case study methodology was applied to document and describe how Lao People's Democratic Republic laid the foundation for the development of a licensing system. The results demonstrate that Lao People's Democratic Republic is currently in the process of transitioning the focus of its HRH policies from the quantity and deployment of services to remote areas to improvements in the quality of services. The key events in the process of developing the licensing system are as follows: (1) the systematic development of relevant policies and legislation, (2) the establishment of responsible organizations and the assignment of responsible leaders, (3) the acceleration of development efforts in response to the Association of Southeast Asian Nations Mutual Recognition Arrangement for standard qualifications, (4) the strengthening of educational systems for fostering competent health care professionals, (5) the introduction of a 3-year compulsory service component in rural areas for newly recruited government servants, and (6) the introduction of a requirement to obtain a professional health care certificate to work in a private hospital. The Lao Ministry of Health (MOH) has endorsed a specific strategy for licensing to realize this system. Conclusion The need for licensing systems has increased in recent years due to regional economic integration and a shift in policy toward achieving universal health coverage. A national licensing system would be a significant milestone in health system development, helping to ensure the competency of health care professionals by means of a national examination, continuing professional development, and the revoking of licenses when appropriate.